2012
DOI: 10.1128/aem.01858-12
|View full text |Cite
|
Sign up to set email alerts
|

OmpA-Mediated Biofilm Formation Is Essential for the Commensal Bacterium Sodalis glossinidius To Colonize the Tsetse Fly Gut

Abstract: Many bacteria successfully colonize animals by forming protective biofilms. Molecular processes that underlie the formation and function of biofilms in pathogenic bacteria are well characterized. In contrast, the relationship between biofilms and host colonization by symbiotic bacteria is less well understood. Tsetse flies (Glossina spp.) house 3 maternally transmitted symbionts, one of which is a commensal (Sodalis glossinidius) found in several host tissues, including the gut. We determined that Sodalis form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 53 publications
5
90
0
1
Order By: Relevance
“…Because A. phagocytophilum colonization reduced the abundance of Gram-positive biofilm-forming species like the Enterococci, we hypothesized that IAFGP alters the tick microbiota by inhibiting bacterial biofilms in the gut. Biofilms have been demonstrated to serve important roles in facilitating pathogen colonization in arthropod intestines (12)(13)(14). To elucidate the importance of IAFGP in shaping the tick gut microbiota, we injected the antibiofilm peptide, P1, derived from IAFGP (25), and showed that this improved A. phagocytophilum infection, in ticks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because A. phagocytophilum colonization reduced the abundance of Gram-positive biofilm-forming species like the Enterococci, we hypothesized that IAFGP alters the tick microbiota by inhibiting bacterial biofilms in the gut. Biofilms have been demonstrated to serve important roles in facilitating pathogen colonization in arthropod intestines (12)(13)(14). To elucidate the importance of IAFGP in shaping the tick gut microbiota, we injected the antibiofilm peptide, P1, derived from IAFGP (25), and showed that this improved A. phagocytophilum infection, in ticks.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota of arthropods and mammals has long been associated with robust biofilms (12,28). To further explore whether altering the biofilm has an effect on the whole tick gut microbial community, we compared the microbiota profiles of P1-injected and sP1-injected ticks.…”
Section: The Peritrophic Matrix Is Essential For Colonization Of the mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Sodalis has modified its outer membrane protein A (OmpA), which represents a molecular adaptation that contributes to host immune tolerance (68). The OmpA protein is also utilized in biofilm production within the tsetse gut, further protecting Sodalis from host immune responses (69).…”
Section: Tsetse Microbial Communitymentioning
confidence: 99%
“…Second, the defect in biofilm formation was another in vitro phenotype exhibited by the purL mutant (Figure 2c). Bacterial biofilm formation is one of the adaptation mechanisms to various environments and has been reported to be required for chronic infections and symbioses (Costerton et al, 2003;Ramey et al, 2004;Visick, 2009;An and Grewal, 2010;Burmølle et al, 2010;Morris and Visick, 2010;Rinaudi and Giordano, 2010;Maltz et al, 2012). In squid-Vibrio symbiosis, Vibrio fischeri uses a transient biofilm to colonize its host, Euprymna scolope (Visick, 2009;Morris and Visick, 2010).…”
Section: Discussionmentioning
confidence: 99%